Effects of increased transaldolase activity on D-xylulose and D-glucose metabolism in Saccharomyces cerevisiae cell extracts. - Senac, T (1991)
In vitro metabolism of D-xylulose and D-glucose in extracts obtained from D-glucose- and D-xylulose-fermenting Saccharomyces cerevisiae cells was investigated with 10- and 100-fold-increased activity of the enzyme transaldolase (EC 2.2.1.2). The rate of sugar consumption was the same in most cases, whereas the rate of ethanol formation decreased with increased levels of transaldolase. The formation of glycerol, pentitols, and acetic acid was not dependent on added transaldolase but was dependent on the sugar used as the growth substrate and on the sugar used in the in vitro metabolism experiments. The carbon balance showed that the dissimilated carbon could not be accounted for in products when transaldolase was added. The concentration of D-fructose-1,6.-diphosphate in the extracts was not influenced by added transaldolase but was higher with D-xylulose than with D-glucose. Levels of pyruvate, comparable with the two substrates, decreased with increasing levels of transaldolase. Exogenously added transaldolase decreased D-sedoheptulose-7-phosphate levels when D-xylulose was the substrate. The results are discussed in relation to the dissimilation of carbon through the upper part of glycolysis and the pentose phosphate pathway.